Ethno-STEAM/STEM in Chemistry Education: A Literature Review of Instructional Models, Digital Learning Resources, and Their Effects on Chemical Literacy and Critical Thinking - Munawwarah,; Side, Sumiati (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study presents a literature review of Ethno-STEAM/Ethno-STEM in chemistry education, focusing on instructional models, digital learning resources, and reported effects on chemical literacy and critical thinking from 2021 to 2025. The review employed a systematic search, screening, and selection procedure aligned with the PRISMA 2020 guideline, followed by a qualitative synthesis using thematic analysis and narrative comparative synthesis. Searches were conducted in Scopus (n = 10), Web of Science (n = 10), and SINTA (n = 30). Following PRISMA 2020, 50 records were identified, 12 duplicates were removed, 38 records were screened by title and abstract, 22 full texts were assessed for eligibility, and 15 studies were included in the qualitative synthesis. The findings indicate that the corpus is dominated by development-oriented (R&D) studies emphasizing the design of digitally supported learning resources—most commonly e-modules and e-worksheets/e-LKPD—alongside a smaller number of empirical studies and review evidence (SLR/meta-analysis). Ethno-STEAM/Ethno-STEM is operationalized through multiple pedagogical pathways, primarily inquiry-based approaches (guided/blended inquiry), project/problem-based learning (PjBL/PBL), practicum-oriented learning (including e-lab designs), and culturally responsive teaching. Local wisdom and cultural practices are typically positioned as a contextual foundation for mapping cultural phenomena onto chemistry concepts and for structuring investigation, design, and communication tasks aligned with STEAM practices. Outcome synthesis suggests more consistent support for critical thinking improvement, whereas direct evidence for chemical literacy remains comparatively limited and constrained by variability in outcome measurement and reporting. The review highlights the need for more robust empirical evaluations with clearer reporting of instructional syntax and implementation fidelity, as well as more standardized measurement of chemical literacy and critical thinking.